Tata Kelola Terhadap Layanan IT Di Kejaksaan Tinggi Kep. Babel Berdasarkan Perspektif Internal Pada Cobit 5 - Liza Fahreni; Edi Surya Negara; Yesi Novaria Kunang (UNIVERSITAS INDO GLOBAL MANDIRI)
So far, the High Prosecutor's Office for Bangka Belitung Islands has not yet had a certain standard in evaluating service levels. In addition, there has never been an evaluation of governance at the service level at the High Court of Bangka Belitung Islands. In this study, the problem faced is the absence of a standardized governance system both in the management and procurement of IT equipment in each work unit, making it difficult to handle problems for each user. This is because basically services require certain effectiveness in terms of time and quality of services and optimize public service tasks in the legal field. In research using a framework to assess IT governance is Cobit 5. Where Cobit 5 can be the basis for assessment. Based on the results of the analysis using the Cobit 5 framework method using 4 domains, namely APO, EDM, BAI and MEA. The assessment uses the help of a maturity model scale, to see the current maturity level conditions. After obtaining the value of the maturity level, it will be seen in which part is needed to improve first. Thus, the results of this research provide priority domains for improvement. Keywords : IT Governance, COBIT 5, Technology Services